Semantinė apibrėžtumo / neapibrėžtumo kategorija (lietuvių ir lenklĮ kalbose) - Roszko, Roman (Respectus Philologicus, 2002)
In traditional linguistics, the category of definiteness / indefiniteness is described by the so-called system of grammatical / morphological oppositions. The components of such oppositions are usually forms with the definite article to express definiteness, and forms with the indefinite article to convey indefiniteness. Using generally accepted definitions of logical quantifiers and the iota operator, in our researches we employ three basic notions whose meanings involve linguistic exponents of logical quantification (Rasiowa) and of definite description (Russell).The category of definiteness / indefiniteness is the category of the sentence (not only of nominal group). By uniqueness we understand an expression of form (tx)P(x) and (1x)P(x), by existentiality - (3x)P(x), by universality (Ax)P(x). In every language uniqueness, existentiality and universality can be expressed on the lexical, morphological and syntactical level (in nominal and verbal group). Means for expressing the definiteness / indefiniteness category in the verbal group in Lithuanian have not been classified at all.
Keywords: apibrėžtumo l neapibrėžtumo kategorija; sinchroninė kalbotyra; kalbą gretinimas; situacinė semantika; kalbos funkcija